Production potential, technology gap and economic analysis of cultivated mushrooms in Kangra district of Himachal Pradesh - Dhiman, Riya; Sud, Deepika (Mushroom Research, 2023)
The study was conducted in five blocks in Kangra district of Himachal Pradesh which fall in two agro-climatic zones i.e. zone I and II. The technology gap showed that there was potential for improving mushroom production in the research area. The net returns from mushroom farming were significantly higher than those from cereals and other crops. Utilization of disinfectants and inputs like spawn over recommended quantities was noted as a positive technology gap.